Isometric handgrip exercise impacts only on very short-term blood pressure variability, but not on short-term blood pressure variability in hypertensive individuals: A randomized controlled trial - Bertoletti, Otávio A.; Ferrari, Rodrigo; Ferlin, Elton L.; Barcellos, Ozi M.; Fuchs, Sandra C. (Frontiers in Physiology, 2022)
Background The effect of a single session of isometric handgrip exercise (IHG) on blood pressure (BP) variability (BPV) has not been addressed. In this randomized controlled trial, we evaluated the effect of IHG vs. sham on BPV in hypertensive individuals. Methods Hypertensive patients using up to two BP-lowering medications were randomly assigned to IHG (4 x 2 min at 30% of maximal voluntary contraction (MVC), with 1 min rest between sets, unilateral) or sham (identical protocol, but with an average intensity of 0.3% of MVC). Systolic and diastolic BP were assessed beat-to-beat in the laboratory before, during, and after the intervention and using 24-hour ambulatory BP monitoring (ABPM). BPV was expressed as average real variability (ARV) and standard deviation (SD). Results In the laboratory, ARV and SD variability increased during exercise and decreased afterward but did not reach baseline values at 15 min into the recovery period. Similarly, systolic BP increased (exercise group 165.4 ± 4.5 vs. 152.4 ± 3.5 mmHg control group; P = 0.02) and diastolic BP increased (exercise group 104.0 ± 2.5 vs. 90.5 ± 1.7 mmHg control group; P < 0.001) then decreased thereafter. However, short-term variability differences between groups (expressed as ARV and SD of systolic and diastolic BP) did not reach statistical significance in the assessment using ABPM. Conclusion A single session of IHG has a very short effect on BPV and does not reduce its short-term variability. Isometric exercise does not affect systolic and diastolic 24 h-BP post-exercise.